2006
DOI: 10.1590/s1415-54192006000300010
|View full text |Cite
|
Sign up to set email alerts
|

A influência do jateamento na cimentação de bandas ortodônticas

Abstract: OBJETIVO: comparar a resistência ao cisalhamento de cinco materiais utilizados na cimentação de bandas ortodônticas: um cimento de ionômero de vidro convencional (Ketac Cem), dois cimentos de ionômero de vidro modificados por resina (3M Multicure Glass Ionomer Cement e Fuji Ortho LC) e duas resinas compostas modificadas por poliácidos (Ultra Band-Lok e Transbond Plus). METODOLOGIA: sobre a superfície de um segmento de banda (6 x 6mm) foi posicionada uma matriz com um orifício de 3mm de diâmetro na qual foi ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In the analysis of shear bond strength, Multi-Cure Glass Ionomer showed higher values than others, however, with no significant difference. Similar results were already observed by Weissheimer et al 23,24 These materials have no chemical union to the metal, so these results may be explained for the greater mechanical imbrication presented by these materials. 5,9,12,13 In the initial proposition of the study, the analysis of cement remnant on the enamel surface after the shear test would be performed.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the analysis of shear bond strength, Multi-Cure Glass Ionomer showed higher values than others, however, with no significant difference. Similar results were already observed by Weissheimer et al 23,24 These materials have no chemical union to the metal, so these results may be explained for the greater mechanical imbrication presented by these materials. 5,9,12,13 In the initial proposition of the study, the analysis of cement remnant on the enamel surface after the shear test would be performed.…”
Section: Discussionsupporting
confidence: 89%
“…20,26 Furthermore, these materials are light cured, which reduces the total setting time and prevents larger exposure to moisture. 8,12,15,23,24 The conventional glass ionomer cements showed similar results and only the microhardness for Meron was significantly higher than Ketac Cem. Unlike these results, Aguiar et al 2 observed better mechanical properties of conventional GIC Ketac Cem in comparison to Meron, however, these authors did not analyze the microhardness of the materials.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations